2011
DOI: 10.1002/jnr.22783
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid modulates inflammatory and antineurogenic functions of activated microglial cells

Abstract: The complex process of microglial activation encompasses several functional activation states associated either with neurotoxic/antineurogenic or with neurotrophic/proneurogenic properties, depending mainly on the extent of activation and the nature of the activating stimuli. Several studies have demonstrated that acute exposure to the prototypical activating agent lipopolysaccharide (LPS) confers antineurogenic properties upon microglial cells. Acutely activated microglia ortheir conditioned media (CM) reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 76 publications
2
36
0
Order By: Relevance
“…Increased neurogenesis in the subgranular zone of the hippocampus in young mice (Valente et al, 2009), and in cell culture (Antonietta Ajmone-Cat et al, 2012), have previously been shown to occur with Ω-3 supplementation. This is likely to occur through increased BDNF levels (Jiang et al, 2009), while Ω-3 deprivation has previously been shown to decrease BDNF and phosphorylated CMP response element binding protein (pCREB) (Bhatia et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased neurogenesis in the subgranular zone of the hippocampus in young mice (Valente et al, 2009), and in cell culture (Antonietta Ajmone-Cat et al, 2012), have previously been shown to occur with Ω-3 supplementation. This is likely to occur through increased BDNF levels (Jiang et al, 2009), while Ω-3 deprivation has previously been shown to decrease BDNF and phosphorylated CMP response element binding protein (pCREB) (Bhatia et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This is likely to predominantly occur through increased Ω-3 displacing Ω-6 from the common metabolic enzyme pathway leading to increased Ω-3 derived prostaglandins, leukotrienes, and thromboxanes which are less pro-inflammatory than their Ω-6 derived counterparts (Tassoni et al, 2008; Farooqui, 2009; Wall et al, 2010). Additionally, cell culture studies have demonstrated that Ω-3 down regulates the p38 MAPK signaling pathway resulting in decreased nitric oxide synthase, decreasing nitric oxide, TNF-α and prostaglandin E2 (Antonietta Ajmone-Cat et al, 2012). Furthermore, Ω-3 promotes the production of peroxisome proliferator-activated receptor (PPAR)-γ, which is known to regulate microglia and astrocyte cytokine production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, docosahexaenoic acid (DHA), one of the most abundant PUFAs in the brain and a potent immunomodulator, was shown to prevent LPS-induced cytokine production in microglia, by directly inhibiting the surface presentation of CD14 and TLR4 (De Smedt-Peyrusse et al, 2008). A growing literature provides evidence for a direct role of DHA in regulating microglial activity (Antonietta Ajmone-Cat et al, 2012; Chen et al, 2014; Chang et al, 2015; Baufeld et al, 2016; Hao et al, 2016; Hopperton et al, 2016; Tremblay et al, 2016). …”
Section: Microglial Perturbations During Brain Developmentmentioning
confidence: 99%
“…It has been demonstrated that DHA inhibits p38 mitogen-activated protein kinase (p38 MAPK) phosphorylation, which consequently inhibits the expression of inflammatory molecules in microglia (Lu et al, 2013) as well as activating PPARγ to modulate microglial inflammatory response (Antonietta Ajimone-Cat et al, 2012). It is now known that such regulation comes not from DHA itself, but from its derivatives (Heras-Sandoval et al, 2016).…”
Section: 0 Dha In Aging Brainmentioning
confidence: 99%